Exploring the effects of work environment variables on the job satisfaction of Nigerian correctional staff. Issue 2 (3rd April 2018) - Elechi, O. Oko; Lambert, Eric G.; Otu, Smart
Abstract: Correctional staff job satisfaction is critical for the staff's well-being and low turnover. This study's focus was identifying variables that predicted job satisfaction for Nigerian correctional staff and comparing the findings to past studies of US correctional staff job satisfaction. One hundred and twenty correctional staff from Nigeria were surveyed. The personal characteristics of age, gender, and tenure were not significant predictors of satisfaction in the multivariate analysis. Similar to finding for US correctional staff, job autonomy, quality of supervision, and instrumental communication all had significant positive effects on Nigerian correctional staff job satisfaction. Contrary to previous findings on US prison staff, neither job variety or role overload were significant predictors of Nigerian staff job satisfaction. Other factors may account for this discrepancy, including working conditions, the socio-economic environment and availability of job opportunities.